Implementasi Website pada Lanang Kreatif Menggunakan Metode WDLC - Muhammad Rivaldy Hisham (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2021)
About 196.7 million internet users have increased from 171.2 million according to a survey conducted by APJII, due to the COVID-19 pandemic effect which’s came from the public to keep their distance from the crowd, switching from being one with the crowd to becoming a personal individual and inevitably want to have to use the rapidly growing technology that’s happening all whole world, the website population that is pushed because the virus spreads causes an increase in website usage to increase significantly which is a new way or method for business owners or MSMEs to switch to using information technology and information systems. The methodology used is a literature review, interviews, observation, system development, and also the web development life cycle, namely by analyzing data after the data is collected, preparing the website for development, and not forgetting to also maintain the website that has been made in such away. Of course, the increase in income at Warung Mbah Lanang Banyuwangi (Lanang Kreatif) will not be wasted by Mr. Joko Seno by facilitating the marketing strategy using Word Of Mouth (WOM), only needing to provide a link to the Warung Mbah Lanang Banyuwangi website.